Adolescents’ Experiences When Living With a Parent With Cancer: A Qualitative Study - Azarbarzin, Mehrdad (Iran Red Crescent Med J, 2016)
BACKGROUND: Cancer affects not only the patient but also their entire family, especially adolescents. Adolescents whose parents are ill may manifest their distress through changes in school performance, physical complaints of pain and discomfort, as well as changes in social and interpersonal relations. There has been very little research about the effects of cancer on adolescents in Iran. OBJECTIVES: The purpose of this qualitative study was to explore the Iranian adolescents’ experiences when living with a parent with cancer. PATIENTS AND METHODS: In this research, the descriptive-explorative approach was used. There were a total of 27 participants. Purposeful sampling was used and data collection methods were semi-structured deep interviews. Constant comparative analysis was used to study the data. RESULTS: The findings of this study showed that the main experiences of these adolescents were categorized into seven themes: 1- psychological problems of adolescents; 2- supportive-educative needs; 3- cancer as a two edged sword in family relationships; 4- stages of confrontation with the parent’s cancer; 5- effect of cancer on social dimensions; 6- affective and helpful supportive agents; 7- Need of support for education under special conditions. CONCLUSIONS: This research showed that Iranian adolescents had the same experiences as other adolescents in other countries in many aspects yet in some issues, such as religious strategy, they had strong religious beliefs that would help them cope with their parents’ cancer. Also it was shown that we must plan a program in which education and support should be provided to enable adolescents to cope with this detrimental situation with minimal disruption.